Production, Purification and Characterization of Laccase from Pleurotus ostreatus - Ghassan M. Sulaiman (Journal of Global Pharma Technology, 2016)
Laccases are a model for multi copper oxidases and contribute in several applications such as biopulping textile, bioremediation, food industries and pharmaceutical compounds. In this work, factorial parameter was used to study the optimization of production conditions yielded an enzyme .The fungal laccase which produced by Pleurotus ostreatus using barley bran under optimization condition by solid state fermentation was purified by DEAE-Cellulose (IEXC) and this purified laccase enzyme was effected to pH and temperatures to determine the pH optimum and temperatures for laccase activity using syringaldazine as substrate. Results showed that the optimal conditions for enzyme production were incubation temperature: 35 oC, inoculum size: 3mm discs moisture ratio: 1: 10 W\V, Incubation period: 22 days. Whereas the optimal enzyme activity was at temperature 45°c and the enzyme remain stable at the same temperature.  Further the optimal pH for enzyme activity at 5.6 and more stable in pH 6.6.Keywords: Laccase, Pleurotus ostreatus, Optimization, Laccase production.